An Investigation of Error Made by Students Based on Their Gender in Writing Narrative Text - Syafiqah Salma Attaqiy; Hesti Wahyuni Anggraini (TELL - US JOURNAL, 2025)
This study aims to investigate the types and frequencies of writing errors made by male and female students at SMAN 2 Indralaya Utara in composing narrative texts and to examine whether there is a significant difference in their writing performance based on gender. Employing a quantitative descriptive design with a comparative approach, the research involved 100 students (50 males and 50 females) selected through stratified random sampling. The students’ works were analyzed using Dulay, Burt, and Krashen’s (1982) surface strategy taxonomy, covering omission, addition, misformation, and misordering errors, while their overall writing performance was assessed through a rubric-based scoring system. The findings revealed that male students produced 305 errors with misformation as the most frequent type (53.77%), while female students made 167 errors, predominantly omission (40.72%). Results from the Independent Samples t-test indicated a significant difference in writing scores, where female students outperformed male students by an average of 7.251 points. The study concludes that gender influences students’ error patterns and narrative writing performance, highlighting the need for gender-sensitive teaching strategies in EFL classrooms.